Liquefaction risks on bulk cargoes carrying Bukit Goh bauxite in accordance International Maritime Solid Bulk Cargoes (IMSBC) code - Syazwan, Sukri (2017)
Bauxite ore is a primary raw material that needed and required in the aluminium production. Among the places that discovered the mining area at Bukit Goh, Kuantan district of Pahang. The findings will be collected and will export to manufacturing countries such as China. Undoubtedly, the discovery of bauxite is a bit much able to improve the economy of the local population and the country but it is also detrimental either to the public or the environment. One of the disadvantages of bauxite is that it can lead to the occurrence of liquefaction on cargo vessels that carry this unprocessed raw material. This study is to focus on the liquefaction risk on bulk cargoes carrying Bukit Goh bauxite in accordance International Maritime Solid Bulk Cargoes (IMSBC) Code. Bauxite ore which mainly contains fine particle and high humidity is vulnerable to the risk of cargo ship liquefaction during the export process of the raw material. The main objective of this study to the analysis of raw and processed bauxite where its fine particle contents have been minimized using beneficiation method to reduce the risk of liquefaction in bulk cargo. For doing this research, five samples was selected from Bukit Goh, Kuantan and taken to the laboratory for testing to determine the geotechnical properties according to the Geospec 3: Model Specification for Soil Testing; particle size distribution, moisture content, specific gravity, morphological properties as well as its elemental and oxide properties. Three samples was taken from the Bukit Goh mine and another two samples from a stockpile. Among the laboratory tests involved in this experiment including Small Pycnometer test, Dry Sieve test, Specific Gravity test, X-ray fluorescence test (XRF) and Field emission scanning electron microscopy test (FESEM). As conclusion form, this research shows the level of bauxite quality that has been processed well than raw bauxite and it is safer to be exported out through bulk cargo.